Evaluation of Nutrient Intake in Bipolar Disorder I Patients According to Body Mass Index Level: A Pilot Study - Alim, Nural Erzurum; Demir, Gülbin; Dundar , Selin; Turk Fidan, Öykü Peren; Coker, Fatma (Progress in Nutrition, 2020)
Background: Bipolar disorders (BD) are severe psychiatric disorders defined by variable mania or hypomania attacks, depression, or mixtures of manic and depressive features. Bipolar disorder I (BDI) is associated with obesity and nutrition. Objectives: To determine the nutritional status and evaluate the anthropometric measurements of BDI patients at Samsun Mental Health and Diseases Hospital. Subjects and methods: This case-controlled study was carried out among 50 BDI patients and 38 normal healthy volunteer individuals. Food frequency questionnaire was applied to the participants and anthropometric measurements were determined. Biochemical tests were retrospectively performed. Results: The mean energy, protein, and Omega 6 intake of the BDI group was significantly higher than the control group (p < 0.05). The mean waist circumference, waist/height ratio, and the frequency of obesity in the BDI group were statistically higher than the control group (p < 0.05). Hemoglobin, triglyceride, CRP, and T3 were significantly higher in the BDI group compared to the control group (p < 0.05). Protein, lipid, carbohydrate, and fiber intake of the individuals differed according to their health status (p = 0.016, p < 0.001, p < 0.001, p = 0.007, respectively). At the same time, the interaction between health status and BMI levels was also significant (p = 0.019). Conclusions: The data obtained may help assess the nutrition of BDI patients. Nutritional assessment should be a part of the plan of care in BDI patients.